1997
DOI: 10.1007/bf02458076
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effect of cytochromec under conditions of prolonged immobilization stress

Abstract: Prolonged immobilization stress activates lipid peroxidation, causes ischemic damage to the myocardium, and promotes the development of some manifestations of atherosclerosis in rabbits. Intravenous infusion of cytochrome c (1 mg/kg) during 30 days of immobilization lowers the extent of lipid peroxidation and produces cardio-and endothelium-protective effects.Key Words: prolonged immobilization stress; cytochrome c; arteriosclerosisThe development of poststress complications caused by prolonged influence of da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Thus, while 3-h immobilization increased superoxide dismutase activity in liver tissues in rats 39 h after stress, it decreased at all time points after 12-h immobilization. Suppression of enzyme activity was seen with prolonged immobilization [6], due to the inhibitory actions of excess malondialdehyde and acylhydroperoxide concentrations and possible structural changes to the enzyme molecule resulting from glycosylation [4,15].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, while 3-h immobilization increased superoxide dismutase activity in liver tissues in rats 39 h after stress, it decreased at all time points after 12-h immobilization. Suppression of enzyme activity was seen with prolonged immobilization [6], due to the inhibitory actions of excess malondialdehyde and acylhydroperoxide concentrations and possible structural changes to the enzyme molecule resulting from glycosylation [4,15].…”
Section: Resultsmentioning
confidence: 99%
“…The control group showed a decrease in the activity of antioxidant enzymes: SOD and catalase. Suppression of SOD activity apparently develops due to the toxic effects of excess MDA and AHP in acute periodontitis, as well as due to possible structural changes in the enzyme molecule, in particular, its glycation (Zorkina et al 1997). The decrease in catalase activity can be explained by the depletion of the enzyme when exposed to an excess of free radicals.…”
Section: Resultsmentioning
confidence: 99%
“…A decrease in the activities of both SOD and catalase, both in plasma and in liver tissue in the course of simulated chronic stress, confirms the conclusion that the activity of antioxidant enzymes is inhibited during prolonged exposure to a stress factor. It was previously shown that the suppression of catalase activity is observed at the time of prolonged immobilization, which is due to the inhibitory effect of excessive concentrations of MDA and AGP, as well as possible structural changes in the enzyme molecule as a result of its glycation (Zor'kina et al 1997).…”
Section: Resultsmentioning
confidence: 99%